Estimating the Effective Lower Bound for the Czech National Bank's Policy Rate - Dominika Kolcunova; Tomas Havranek (Czech National Bank, 2018)
The paper focuses on the estimation of the effective lower bound for the Czech National Bank's policy rate. The effective lower bound is determined by the value below which holding and using cash would be more convenient than deposits with negative yields. This bound is approximated based on storage, the insurance and transportation costs of cash and the costs associated with the loss of the convenience of cashless payments and complemented with the estimate based on interest charges, which present direct costs to the profitability of the bank. Overall, the estimated value is below -1% and is approximately in the interval -1.6%, -1.1%. In addition, by means of a vector autoregression, we show that the potential of negative rates would not be sufficient to deliver monetary policy easing with effects similar to those of the exchange rate commitment.
Keywords: E52; E58; 330; effective lower bound; negative interest rates; costs of holding cash; transmission of monetary policy